Readiness for competition across sports and genders: a study on psychological skills intervention - Alecu Stefan; Onea Gheorghe Adrian (My University, 2025)
Introduction: Psychological readiness is essential for athletic performance, particularly under competitive pressure. While physical training remains critical, growing evidence supports the role of psychological interventions in enhancing motivation and managing pre-competition anxiety. This study, grounded in Self-Determination Theory (SDT), evaluates the effects of a structured 4-week psychological program on athletes’ motivation and anxiety levels. Materials and methods: A total of 512 athletes (210 individual-sport, 302 team sport; 280 women, 232 men) completed the Sport Motivation Scale-II (SMS-II) and the Competitive State Anxiety Inventory-2 (CSAI-2) before and after a 4-week intervention. The program included goal-setting, visualization, mindfulness, and team cohesion sessions, delivered by certified sport psychologists and applied by coaches. Data were analyzed using mixed ANOVAs, t-tests, Bonferroni correction, and effect size estimates (Cohen’s d, η2). Results: Post-intervention results showed substantial improvement in intrinsic, integrated, and identified motivation, alongside decreases in introjected and external regulation and amotivation (p < 0.001). Athletes also experienced significant reductions in cognitive and somatic anxiety and increased self confidence. These effects were large (d > 0.8) and consistent across gender and sport types; however, no interaction effects remained reliable after correction.Conclusion: A brief psychological intervention can significantly improve motivational regulation and competitive readiness across diverse athlete groups. These findings highlight the value of integrating mental skills training into routine sport preparation and support the implementation of scalable, evidence-based psychological programs
Keywords: sport motivation; readiness for competition; mental skills training; competitive anxiety; psychological intervention